The Utilization of Media Technology in Industrial Transformation and Development of Local Creative Industries - Irfan Fauzi (International Journal of Technology and Education Research, 2024)
This research aims to describe the use of media technology in industrial transformation and development of local creative industries. The qualitative method is a method that focuses on in-depth observation. Therefore, the use of qualitative methods in research can produce a more comprehensive study of a phenomenon. The research method used in this article is. Case Study: In this method, researchers will take several examples of businesses that have successfully adopted technology in their business, and analyze how technology plays a role in industrial transformation. Research results Technology has had a significant impact on the way businesses operate Technology has made it possible to increase efficiency and productivity by reducing the costs and time required to run business operations. The application of technology also helps in accelerating innovation and developing better products, so that they can compete better in the market. The use of technology must be considered carefully. The role of digital media which is used for everyone's various needs in the current digital era is growing quite large, especially digital marketing which is utilized by companies or personal businesses in terms of the marketing process for industrial products, especially the creative industry.